lncRNA DARS-AS1 Modulates TSPAN1-Mediated ITGA2 Hypomethylation by Interaction with miR-194-5p Thus Promoting Ovarian Cancer Progression - Jun Li; Haoyu Gao; Beibei Chen; Li Li; Qianqing Wang; Zhihui Gao (Stem Cells International)
Objective. Ovarian cancer (OC) is usually called the “silent killer” due to its asymptomatic characteristics until advanced stages, thus being a significant threat to female health worldwide. In this work, we characterized an oncogenic DARS-AS1 role in OC. Methods. The aggressiveness behaviors of the OC cell model were examined by CCK-8 assay, transwell invasion assay, flow cytometry, and immunoblotting analysis of apoptosis-related proteins. Interactions of miR-194-5p with lncRNA DARS-AS1 or TSPAN1 and of TSPAN1 with ITGA2 were validated by using a luciferase activity assay and chromatin immunoprecipitation (ChIP) assay. Results. The OC cell model exhibited overexpressed lncRNA DARS-AS1 compared to normal cells. lncRNA DARS-AS1 knockdown led to reduced OC cell growth and metastasis while inducing the apoptosis in the OC cell model. lncRNA DARS-AS1 positively regulated TSPAN1 expression by binding with miR-194-5p and TSPAN1-mediated ITGA2 hypomethylation in OC cells. Further rescue function studies demonstrated that lncRNA DARS-AS1 affected OC cell viability, migration, invasion, and apoptosis ability by modulating miR-194-5p and TSPAN1 expressions. Conclusion. Our work demonstrates that lncRNA DARS-AS1 promotes OC progression by modulating TSPAN1 and ITGA2 hypomethylation by binding with miR-194-5p.